(untitled) (Journal of Libya for geographical studies, 2026)
This study focuses on the application of the Topographic Wetness Index (TWI) as a Geographic Information Systems (GIS) and Remote Sensing–based approach to analyze the relationship between terrain water retention potential and surface runoff convergence toward low-lying areas. The coastal region of Al-Khums is bounded to the south by a series of elevated plateaus and hills and dissected by numerous wadis, making it highly susceptible during rainy seasons to the accumulation of large volumes of rainfall in topographic depressions. This often results in flash floods that cause road closures and disrupt traffic movement across the region. Accordingly, the study aimed to analyze the influence of topographic characteristics on the spatial distribution of surface runoff and to identify areas most vulnerable to flash flood accumulation, while establishing a digital geographic database that can be utilized in urban planning and flood risk mitigation. The results demonstrated that flood occurrences are clearly concentrated along major road networks, posing significant threats to population safety, built-up areas, and transportation continuity. Furthermore, the Topographic Wetness Index (TWI) proved to be highly effective in accurately delineating water accumulation zones, confirming its importance as a robust scientific tool for predicting flood-prone areas and supporting decision-makers in water resources management, flood mitigation, and sustainable urban planning within the study area.